Pertunjukan Tayub Sebagai Sarana Ritual Pernikahan Di Karangmojo Jenar Sragen - Eko Wahyu Prihantoro (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2018)
Karangmojo Village, Sub District Jenar, District  Sragen has a unique tradition namely a ritual conducted by local community. This ritual is held to celebrate a wedding ceremony by performing Tayub. This research aims to: a) describe the wedding ceremony at Karangmojo Village by performing Tayub as its ritual means, b) interprete the meaning of movements and melody (gendhing) in Tayub dance.  The style of this research is interpretative discription of aqualitative nature. The first step in this research is data collection trough field study , observation and interviews, and the scond step is data processing by analyzing qualitatively the form, function and meaning. Those steps are applied consecutively beginning from reduction, data reformation or display, and ending in conclusion. This research uses  a holistic approach involving all aspects in performing art. The research result shows that the performance is meant as a gratitude and request  to God hopping that the wedding will last eternally, be blessed, and be protected against disturbance, be granted all desire, have a child and happiness.Keywords: ritual, Tayub, meaning,Sragen.   Pengantar